Forming limit diagram of Advanced High Strength Steels (AHSS) based on strain-path diagram. (15th November 2015) - Bhargava, Marrapu; Tewari, Asim; Mishra, Sushil K.
Abstract: Advanced High Strength Steels (AHSS) is a promising material for automotive applications due to its high strength-to-weight ratio compared to other steels. Recently third generation steels have been developed which show intermediate properties between first and second generation AHSS. Formability analysis was performed between first generation Transformation Induced Plasticity (TRIP) and second generation Quenched and Partitioned (Q&P) AHSS. The main objective of the study is to perform formability analysis of TRIP and Q&P AHSS. The chemical compositions of both the steels are almost similar but different processing conditions lead to microstructural variations. Experimental and simulated strain-path diagram (SPD) was plotted from drawing to stretching regions using Limit Dome Height (LDH) test and Finite Element Method (FEM) respectively. The formability of TRIP steel is higher when compared to Q&P steels. Stretching regions show large deviation between experimental and simulated SPD for both the steels. A new strain localization criterion is proposed to construct a forming limit curve (FLC) for both experimental and simulated SPD. The proposed failure criterion is compared with other failure criteria for FLC prediction. The FLC based on new strain localization criterion shows better agreement with experimental FLC compared to other failure criteria. Graphical abstract: Highlights: A strain localization criterion was proposed to predict the forming limit curve. The proposed criterion is in well agreement with the experimental forming limit curves. The proposed criterion is better compared to other localization criteria proposed by other researchers. Formability of TRIP steel is higher compared to Q&P steel.